The Influence of Vocabulary Journal towards Students’ Vocabulary Mastery - Purwati, Dwi (English Education: Jurnal Tadris Bahasa Inggris, 2022)
As English is the lingua franca, mastering it is very important. However, the students of SMP N 5 Bandar Lampung were found to have difficulties in developing their English vocabulary due to the teaching strategy used by the teacher. This research was conducted to find out the influence of using vocabulary journal strategy in student’s vocabulary mastery using quasi-experimental design. The research population was the ninth grader of SMP N 5 Bandar Lampung in the academic year of 2021/2022. The research samples were two classes consisting 9G as the experimental class and 9H as the control class. The experiments were held in three meetings for each classes. After getting the data of student’s vocabulary scores from pre-test and post-test, the data were analyzed using SPSS. It was found that Sig. = 0.000 and α = 0.05, so H0 was rejected and Ha was accepted because of Sig. <0.05. Based on the result, it can be concluded that there was a significant influence of using vocabulary journal strategy towards student’s vocabulary mastery of the ninth grader of SMP N 5 Bandar Lampung in the academic year of 2021/2022.